Perforation in a patient with stercoral colitis and diverticulosis: who did it? - Vijaya R. Bhatt; Srujitha Murukutla; Jason DiPoce; Steven Gustafson; David Sarkany; Kokila Mody; Warren D. Widmann; Aaron Gottesman (Greater Baltimore Medical Center, 2014)
Stercoral colitis with perforation of the colon is an uncommon, yet life-threatening cause of the acute abdomen. No one defining symptom exists for stercoral colitis; it may present asymptomatically or with vague symptoms. Diagnostic delay may result in perforation of the colon resulting in complications, even death. Moreover, stercoral perforation of the colon can also present with localized left lower quadrant abdominal pain masquerading as diverticulitis. Diverticular diseases and stercoral colitis share similar pathophysiology; furthermore, they may coexist, further complicating the diagnostic dilemma. The ability to decide the cause of perforation in a patient with both stercoral colitis and diverticulosis has not been discussed. We, therefore, report this case of stercoral perforation in a patient with diverticulosis and include a discussion of the epidemiology, clinical presentation, and a review of helpful diagnostic clues for a rapid differentiation to allow for accurate diagnosis and treatment.